2007
DOI: 10.1124/mol.107.041475
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-α Contributes to the Anti-Inflammatory Activity of Glucocorticoids

Abstract: Glucocorticoids (GCs) are effective anti-inflammatory agents widely used in the therapeutic approach to treatment of acute and chronic inflammatory diseases. Previous results suggest that peroxisome proliferator-activated receptor-␣ (PPAR-␣), an intracellular transcription factor activated by fatty acids, plays a role in the control of inflammation. With the aim of characterizing the role of PPAR-␣ in GC-mediated anti-inflammatory activity, we tested the efficacy of dexamethasone (DEX), a synthetic GC specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 68 publications
1
45
0
3
Order By: Relevance
“…PPARα also has been found to modulate the anti-inflammatory effect of glucocorticoids in inflammatory lung and bowel models in mice. 50,51 Of note, the distinct upregulation of ABCG5 and ABCA1 induced by exogenous CORT suggested the involvement of PPARα-independent regulatory pathways. Particularly, it appeared that high levels of CORT, most likely via a coordinated effect of PPARα and LXRα, exerted redundant effects on the enterocyte net cholesterol balance (ie, by decreasing NPC1L1 gene expression levels and upregulating ABC transporters).…”
Section: Discussionmentioning
confidence: 99%
“…PPARα also has been found to modulate the anti-inflammatory effect of glucocorticoids in inflammatory lung and bowel models in mice. 50,51 Of note, the distinct upregulation of ABCG5 and ABCA1 induced by exogenous CORT suggested the involvement of PPARα-independent regulatory pathways. Particularly, it appeared that high levels of CORT, most likely via a coordinated effect of PPARα and LXRα, exerted redundant effects on the enterocyte net cholesterol balance (ie, by decreasing NPC1L1 gene expression levels and upregulating ABC transporters).…”
Section: Discussionmentioning
confidence: 99%
“…S1C). Recently, Riccardi and colleagues (11) tested the efficacy of DEX in carrageenan-induced pleurisy in PPAR␣ KO and WT mice. These authors found that the DEXmediated antiinflammatory activity was lower in PPAR␣ KO compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, others have shown that activation of PPAR␥ by other microbial ligands induces suppression of host inflammatory responses in vitro and in vivo (22). The presence of PPAR␣ is required for modulation of inflammation following exposure to LPS or sepsis in vivo (23)(24)(25)(26). Therefore, we hypothesized that suppression of inflammatory responses mediated by SchuS4 lipids in macrophages may require either PPAR␥ or PPAR␣.…”
Section: Fig 3 Schus4 Lipid-mediated Modulation Of Inflammatory Respomentioning
confidence: 99%